Pengaruh Lama Waktu Konsumsi Obat Pada Penderita Tb Terhadap Kadar Kreatinin dan Ureum di Laboratorim RSUW UIT Makassar 2018 - Risma Risma; Abdul Rahman (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2020)
Tuberculosis is a specific infectious disease in humans and animals caused by Mycobacterium tubercolosis with a prolonged eradication of the disease causing various reactions to these results. (Soedarto, 1996). This study aims to find out the effect on people who consume OAT on long-term treatment of creatinine and ureum levels.From research conducted from 5 samples showed that the sample still experienced a slight increase in creatini levels but still within normal limits.